Time-Resolved Photoluminescence Spectroscopy Evaluation of CdTe and CdTe/CdS Quantum Dots. (15th October 2012) - Yuan, Zhimin; Yang, Ping; Cao, Yongqiang
Abstract : CdTe and CdTe/CdS quantum dots (QDs) were prepared in aqueous solutions using thioglycolic acid as a stabilizing agent. The photoluminescence (PL) wavelength of the QDs depended strongly on the size of CdTe cores and the thickness of CdS shells. Being kept at room temperature for 130 days, the PL wavelength of CdTe and CdTe/CdS QDs was red-shifted. However the red-shifted degree of CdTe QDs is larger than that of CdTe/CdS QDs. The size of CdTe QDs and the thickness of CdS play important roles for the red-shift of PL spectra of CdTe/CdS QDs. In contrast, the full width at half maximum of PL spectra of CdTe and CdTe/CdS QDs almost remained unchanged. This is ascribed to the effects of Cd 2+ and TGA in solutions on the growth of CdTe and CdTe/CdS QDs. This associated with the variation of surface state of the QDs during store. The results demonstrate that CdTe/CdS core/shell QDs have high stability compared with CdTe QDs due to a CdS shell.